Can we predict Alzheimer’s Disease through the eye lens? - CS, Sandeep; N, Vijayakumar; A, Sukesh Kumar (International Journal of Clinical and Experimental Ophthalmology, 2020)
Alzheimer’s Disease (AD) is a common dementia problem of the old population. The two main hallmarks of AD are tau protein and amyloid-beta protein. The relevant investigations on AD suggest that these proteins are also seen in the eye. There are many tests and imaging modalities are used for AD diagnosis. But these techniques are still unable to predict the disease effectively. In this regard, the lens of the eye may help in diagnosing AD. Therefore, a reliable technique for measuring the lens or retina must be selected. In this paper, we focus on the different types of retinal diseases occur in AD patients and the use of the Optical Coherence Tomography (OCT) technique is used for diagnosing AD.